Phytochemical, Antioxidant Screening, Antinociceptive, and Anti-inflammatory Activities of Boswellia dalzielii Hutch (Burseraceae) Root Ethanol Extract Using Animal Model - MacDonald Idu; Anthonia Omoregbee; Benjamin Ogunma Gabriel (Biology, Medicine, & Natural Product Chemistry, 2023)
This study investigated the biological activities and phytochemical screening of Boswellia dalzielii root ethanol extract. Standard procures were used to evaluate the phytochemicals and antioxidant capacity, antipyretic activity in bakers yeast-induced pyrexia in mice, analgesic property (hotplate and acetic acid-induced in mice), acute antiinflammation (carrageenan-induce in rats) and chronic arthritis (formalininduced in rats) on Boswellia dalzielii root ethanol extract. The phytochemical results revealed the presence of phenol, ascorbic acid, flavonoids, alkaloids, cardiac glycoside, tannin, saponin. The extract had a significant reduction in the body temperature in graded doses and 100 mg/kg paracetamol at 60 minutes when compared with the control, but 400 mg/kg was more effective (p<0.01). Morphine and plant extract showed a slight significant analgesic property at 0 and 30 minute compared to the control. The extract at 100 mg/kg elicited a significant increase at 60 and 90 minutes compared with the control, and it is comparable to 5 mg/kg morphine. The plant extract (100, 200, and 400 mg/kg) and aspirin (100mg/kg) shows significant analgesic properties compared to control (p<0.01) but 200 mg/kg of extract revealed highest percentage inhibition. The extract produced no significant reduction on carrageenan induced inflammatory at all dose level compared to control (p>0.05). The plant extract (100, 200, 400 mg/kg) and Indomethacin (1 mg/kg) reduced paw volume across the doses from day 4 compared to the control (p<0.01). The Boswellia dalzielii root extract is a promising antiinflammatory agent, it also possesses antipyretics, and analgesics effect validating the folklore claim.